2018
DOI: 10.1002/app.46943
|View full text |Cite
|
Sign up to set email alerts
|

Use of acoustic emission in the analysis of polypropylene failure caused by photodegradation

Abstract: Photodegradation is among the most frequent causes for the low performance of polypropylene (PP) products during service. This type of failure has been investigated extensively throughout the years using conventional methods including infrared spectroscopy and molar mass measurements. The use of acoustic emission, conversely, is not a common technique to evaluate polymer behavior, even though showed to be very useful to detect and locate damage during loading, contributing to the understanding and, hence, to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…However, a major different in relation to the unstabilized blends was the absence of visible cracks on the nonexposed faces of the samples with the UVA additive, even at 40 weeks exposure. This was also observed with neat PP [15] and it is supposed to be a consequence of the absorption of ultraviolet radiation at the proximity of the exposed side, making more difficult the UV path to the interior of the sample bar and to the back side. Actually, measurements of the UV intensity at the unexposed side showed that the amount of ultraviolet light at the opposite side of the sample was only 6% of the total UV radiation.…”
Section: Surface Crackingmentioning
confidence: 68%
See 4 more Smart Citations
“…However, a major different in relation to the unstabilized blends was the absence of visible cracks on the nonexposed faces of the samples with the UVA additive, even at 40 weeks exposure. This was also observed with neat PP [15] and it is supposed to be a consequence of the absorption of ultraviolet radiation at the proximity of the exposed side, making more difficult the UV path to the interior of the sample bar and to the back side. Actually, measurements of the UV intensity at the unexposed side showed that the amount of ultraviolet light at the opposite side of the sample was only 6% of the total UV radiation.…”
Section: Surface Crackingmentioning
confidence: 68%
“…This is very similar to what was shown before for neat PP exposed under the same conditions. [15] Besides reducing the mechanical properties, these cracks also damage the physical appearance of the products, turning then useless to the consumer, depending on the application. The cracks are not formed randomly, but show a pattern mainly perpendicular to the flow direction during injection moulding.…”
Section: Surface Crackingmentioning
confidence: 99%
See 3 more Smart Citations